Fabrication and characterization of polycarbonate/titanium oxide nanotubes mixed matrix membranes for efficient removal of cadmium and copper from aqueous solution - M. Delavar; Gh. Bakeri; M. Hosseini (Iranian Journal of Chemical Engineering)
In this study, novel polycarbonate-titanium oxide nanotubes (PC-TNT) ultrafiltration mixed matrix membranes (MMMs) were fabricated for decontamination of Cd2+ and Cu2+ metal ions from aqueous solution. The weight percent of TNTs in the polycarbonate membrane matrix was changed from 0 to 15. The synthesized neat PC membrane and PC-TNTs MMMs were characterized with respect to structural morphology and hydrophilicity using scanning electron microscopy (SEM) and water contact angle, respectively. The effects of TNTs loadings on the pure water flux, mean pore size, porosity and water contact angle of fabricated membranes and Cd2+ and Cu2+ heavy metal ion rejection were also studied. By increasing the loading of TNTs nanoparticles in the membrane matrix, the membrane mean pore size tended to increase, while the porosity decreased. Also, the increase in TNTs loading resulted in an increase in membrane water flux which was mainly attributable to the enhancement in mean pore size and partly caused by the decreased contact angle value (more hydrophilic). Of all the membranes studied, it was found by UF experiments that PC-TNT MMM was the most efficient material in heavy metal ions removal due to the superior adsorption capacity of TNTs material. The generic results revealed that TNTs material can be favorite candidates for MMMs preparation in order to be conveniently used in the Cd2+ and Cu2+ heavy metal ions decontamination from polluted water resources.